Immunohistochemical Study of Scrub Typhus: A Report of Two Cases - Bo-Yuan Tseng (Kaohsiung Journal of Medical Sciences, 2008)
Scrub typhus is a zoonotic disease caused by Orientia tsutsugamushi, which is transmitted by chiggers. The target cells of this rickettsia are poorly defined in humans. Immunohistochemical staining of tissue sections of patients with scrub typhus is helpful in investigating the target cells of this rickettsia in different organs. We studied two autopsy specimens by immunohistochemical staining using a specific antibody against O. tsutsugamushi. Rickettsiae were located in endothelial cells in all of the organs evaluated, namely heart, lung, brain, kidney, appendix and skin, within cardiac muscle cells and renal tubular epithelial cells, and in macrophages located in the lymph node, liver and spleen. In conclusion, O. tsutsugamushi may disseminate into multiple organs through endothelial cells and macrophages, resulting in the development of fatal complications.